The Comparison of Performance Polycrystalline and Amorphous Solar Panels under Malang City Weather Conditions - Witono, Kris; Asrori, Asrori; Harijono, Agus (CV. Creative Tugu Pena, 2021)
Amorphous Silicon type solar panels, which had a bad reputation in the past, are now considered very reliable, with several significant advantages over Mono Crystalline and Polycrystalline solar panels. Research on the effectiveness of the capture power of Amorphous Silicon compared to Silicon Crystalline solar panels types is still not much done.The purpose of this study was to explain the effect of solar radiation on the capture power of polycrystalline and amorphous solar panels.This research method includes solar panel installation, measurement of solar radiation, measurement of the resulting current and voltage, data analysis, discussion, and conclusions. The independent variables of the study were the resulting current and voltage, and the type of solar panels (Polycrystalline and Amorphous). The dependent variable of this research are actual power and efficiency.The results showed that the greater the solar radiation, the higher the actual power and efficiency produced by the solar panels. Polycrystalline type solar panels are capable of producing higher average actual power and average efficiency, namely 86.83 W and 11.92%, compared to amorphous solar panels, namely 43.88 W and 6.01%. Keywords: Monocrystalline, Polycrystalline, Normalized Power Output Efficiency, Performance Ratio